Broadening Low-Frequency Band Gap of Double-Panel Structure Using Locally Resonant Sonic Crystal Comprised of Slot-Type Helmholtz Resonators - KIM, Myong-Jin; RIM, Chun-Gil; WON, Kyong-Su (Archives of Acoustics, 2021)
An approach is presented to form and broaden the low-frequency band gap of the double panel structure (DPS) by using a locally resonant sonic crystal (LRSC) in this work. The LRSC is made of cylindrical Helmholtz resonators arranged on square lattice. Their designs are similar to a slot-type resonator, but have different depths of slot. Elongating the slit neck inward and distributing the depths of slots produce a broad local resonant band gap at low frequencies: an average insertion loss (IL) of 10.9 dB covering 520 Hz to 1160 Hz with a LRSC of 12 cm width. Next, the effect of porous material filled into the resonators on the local resonant band gap is evaluated. It is shown that filling of porous material into the resonators decreases the height and width of the local resonant band gap. Finally, the transmission losses (TLs) through the DPS with LRSC are calculated as a function of the incident angle of the sound wave for LRSC embedded in porous material and not. The results show that the porous material can be significantly reduce the incident angle dependency of TL through the DPS with LRSC.